Maupassant’s tales of war: a type of testimony - Lima, Clarissa Navarro Conceição; Leite, Guacira Marcondes Machado (Lettres Françaises, 2016)
The Franco-Prussian War has left deep traces in the history of the French people, whose homeland was invaded, bombed, humiliated and tormented. The conflict occurred from 1870 to 1871 and, although short, caused many deaths and much destruction. Guy de Maupassant took part in the war when he was young and about ten years later he produced several narratives related to this historical moment. In his short stories about war, the historical memory is present and sustains the whole narrative; this paper discusses, therefore, the question of the testimony without an “I-witness”. The author who has seen and experienced the catastrophe of war also offers his rightful testimony, even if it is masked by images and comparisons. We attempt to prove that the testimony obtained from fiction can also be authentic, since, according to Seligmann-Silva and Octavio Paz, all truth is historical, all literature is testimonial, and every testimony has the maximum credit of truth. In order to do so, this paper is based on theories such as the analysis and the theoretical study of Seligmann-Silva’s History, Memory and Literature: The testimony in the era of catastrophes, among others.